2008
DOI: 10.1128/jvi.01688-08
|View full text |Cite
|
Sign up to set email alerts
|

An Alphavirus Replicon-Based Human Metapneumovirus Vaccine Is Immunogenic and Protective in Mice and Cotton Rats

Abstract: Human metapneumovirus (hMPV) is a recently discovered paramyxovirus that causes upper and lower respiratory tract infections in infants, the elderly, and immunocompromised individuals worldwide. Here, we developed Venezuelan equine encephalitis virus replicon particles (VRPs) encoding hMPV fusion (F) or attachment (G) glycoproteins and evaluated the immunogenicity and protective efficacy of these vaccine candidates in mice and cotton rats. VRPs encoding hMPV F protein, when administered intranasally, induced F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
4
41
0
Order By: Relevance
“…We found that while ␣GC adjuvant was associated with increased IL-4 levels, VLPs alone were not, and VLPs with TMG were associated with increased IL-10 or IFN-␥ levels. Vaccination with recombinant F protein or alphavirus-vectored F was not associated with enhanced disease in cotton rats (23,47). It is important to note that rodent models do not always reflect human biology and that rodents are not faithful models of human respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that while ␣GC adjuvant was associated with increased IL-4 levels, VLPs alone were not, and VLPs with TMG were associated with increased IL-10 or IFN-␥ levels. Vaccination with recombinant F protein or alphavirus-vectored F was not associated with enhanced disease in cotton rats (23,47). It is important to note that rodent models do not always reflect human biology and that rodents are not faithful models of human respiratory disease.…”
Section: Discussionmentioning
confidence: 99%
“…Only the F protein is required for virus assembly, fusion, and entry (13,44). Furthermore, the HMPV F protein is the primary target of neutralizing antibodies (13,23,(45)(46)(47)(48). In contrast, while HMPV G is immunogenic in rodents, G-specific antibodies do not neutralize HMPV and G vaccines provide no protection in animals (47)(48)(49).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, we feel there is not enough information yet to evaluate the predictive value of the NHP efficacy measurements. When the NIAID's TetraVax-DV vaccine was tested in rhesus macaques, it resulted in 100% seroconversion (defined as 4-fold or greater increase in PRNT after immunization) to all 4 serotypes after a single dose of formulation TV-2, with PRNT 60 GMTs of 57,16,18, and 126 to DENV1 to -4, respectively, measured on day 28 postvaccination (64). Challenge with each DENV serotype homologous strain on day 42 resulted in 100% protection from viremia against challenges with DENV1, -3, and -4, but not -2.…”
Section: Discussionmentioning
confidence: 99%
“…VRP target dendritic cells in the draining lymph nodes of immunized animals (52), where amplification of the replicon RNA results in strong induction of innate immunity and the vaccine antigen is expressed in immunogenic amounts (53,54). Alphavirus replicon particle vaccines have been studied extensively in recent years and have conferred protective immunity to a wide variety of viral and bacterial antigens tested in different animal models with an exceptional safety record (55)(56)(57)(58)(59)(60). More importantly, the layered safety features of the VRP system have been assessed in humans in phase I clinical trials of VRP expressing the Gag protein of clade C HIV (61) and cytomegalovirus gB or a pp65/IE1 fusion protein (62).…”
mentioning
confidence: 99%